Islam and the 1 Malaysia concepts - Mohamad, Nor Asiah (2010)
The misunderstanding about the position of Islam as the religion of the Federation of Malaysia continues. Some perceive the provision under article 3 of the Federal Constitution as putting Islam as the official religion of the country while others addressing the permission to practice other religions as providing equal rights to other religions as much as it is allocated for Islam. This paper promotes that 1 Malaysia implies that as the Federal Constitution has clearly defined that Malaysia declares Islam as the religion of the Federation, as such, the position of Islam in higher than other religions. In this respect, this paper traces the aspects of which the government is entrusted to provide and argues that the government is not burdened with a duty to ensure equality of rights and treatment in all aspects concerning religion to others. Thus, the assurance that other religions may be practiced is a permission allowing the non Muslim to embrace their religions without putting a responsibility on the government to ensure equal rights are provided. This paper looks at the meaning and spirit of Article 3 of the Federal Constitution and the rights and duties assigned to the Yang Di Pertuan Agong to protect the position of Islam as the religion of the Federation.